2014
DOI: 10.1016/j.ijid.2014.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Clinical aspects and outcomes of 70 patients with Middle East respiratory syndrome coronavirus infection: a single-center experience in Saudi Arabia

Abstract: MERS-CoV can cause severe infection requiring intensive care and has a high mortality. Concomitant infections and low albumin were found to be predictors of severe infection, while age ≥65 years was the only predictor of increased mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

39
475
6
16

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 454 publications
(536 citation statements)
references
References 20 publications
(30 reference statements)
39
475
6
16
Order By: Relevance
“…This study describes the largest sample of confirmed MERS-CoV cases and confirms previous study findings indicating males are predominately affected by this disease [6,7] and is in comparison to Severe Acute Respiratory Syndrome (SARS), where there is a predominance of females in all cases [8]. Healthcare workers were at high risk and accounted for one-sixth of all cases, in comparison to SARS in which healthcare workers accounted for one-fifth of all cases.…”
Section: Discussionsupporting
confidence: 86%
“…This study describes the largest sample of confirmed MERS-CoV cases and confirms previous study findings indicating males are predominately affected by this disease [6,7] and is in comparison to Severe Acute Respiratory Syndrome (SARS), where there is a predominance of females in all cases [8]. Healthcare workers were at high risk and accounted for one-sixth of all cases, in comparison to SARS in which healthcare workers accounted for one-fifth of all cases.…”
Section: Discussionsupporting
confidence: 86%
“…In one observational study at a single center in Saudi [19]. Severe neurologic syndrome, including altered level of consciousness, ranging from confusion to coma, ataxia, and focal motor deficit, has been reported in three critically ill MERS-CoV patients, with brain magnetic resonance imaging (MRI) showing widespread, bilateral hyperintense lesions on T2-weighted images in the white matter and subcortical areas of different brain areas [27].…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…[4,5,6] Human-tohuman transmission of MERS-CoV is all around recorded in the family, group settings and more frequently in social insurance settings [4,7,8]. As such, bigger hospital outbreaks have been driven by a combination of overdue recognition, over-crowding, and inadequate infection control precautionary measures [6,9,10]. In any case, MERS-CoV between human transmissibility is believed to be moderately restricted.…”
Section: Introductionmentioning
confidence: 99%